The Ratio of the Genome Two Functional Parts Activity as the Prime Cause of Aging - Salnikov, Lev; Baramiya, Mamuka G. (Frontiers in Aging, 2020)
The metazoan genome composes of sets of housekeeping genes (HG) for fundamental cellular autonomous processes and integrative genes (IntG) that provide integrative functions and form the body as an integrated whole. The main paradigm for multicellularity development which has been improved in evolution, is the submission of the cellular autonomy to the interests of the integrated whole. Permanent increase of the “functional tax” of IntG-genome (IntG-shift) and epigenetic restriction of autonomy in phylogenesis/ontogenesis is the essence and root cause of aging, inherent in the very nature of highly integrated multicellularity. The regulation of the balance shift toward HG can be managed to eliminate aging and avoid carcinogenesis, which is only due to the irreversibility of this shift. Here we propose the criterion for measuring the functional and biological age of cells and the body as a whole for assessing the effectiveness of any type of palliative geroprotective or radical anti-aging intervention.